Smart Casing for Desktop Personal Computer (International Journal of Engineering and Computer Science, 2013)
mputer cooling is the process of removing the heat from computer components. Since a computer system's componentsproduce large amounts of heat during operation, this heat must be dissipated in order to keep these components within their safe operatingtemperature. In addition to maintain normal function, varied cooling methods are introduced to either achieve greater processorperformance, or else to reduce the noise pollution caused by typical This project is proposed as to develop a system that can detect thetemperature from the hardware system. This project is a standalone temperature and fan monitoring and control unit for the PersonalComputer (PC). The main objective of this project is to overcome the problem that occurs when the system is running for a long time andtemperature of the hardware is increase. The ability of this project is this project can control and maintain the value of temperature. Thisproject will turn off the main power if the temperature is overheating. LM35S sensors are used to capture two different temperatures anddetect if there are any increases in the temperatures. The main control of this circuit is the Peripheral Interface Controller (PIC) 16F876A tocontrol Direct Current (DC) fans and Light Emitting Diode (LED) when certain temperature was detected. The results showed the systemwas working successfully as the aim in the objectives. For further improvement in the future, this project can be applied in industrial sectore.g. as temperature controllers in industry include plastic extrusion and injection molding machines and thermo-forming machi